THE FACTORS OF THE EIGHTH GRADE STUDENTS’ PROBLEMS IN WRITING RECOUNT TEXT AT SMP NEGERI 12 KOTABUMI ACADEMIC YEAR 2022/2023 - Rulik Setiani; Mutia Restika; Rini Susilowati (Language and Education Journal, 2023)
The aim of this study was to explain the whole factors and the most dominant factor causing the eighth grade students’ problems in writing recount text at SMP Negeri 12 Kotabumi Academic Year 2022/2023. This study used a descriptive-qualitative method. The document was used as a data which examined 27 students’ writing recount text by taking 6 students who have the lowest score. The research findings showed that the students have linguistic problems: grammar 23 errors, vocabulary 2 errors, and choice of sentence no error, in cognitive problems: punctuation 18 errors, capitalization 4 errors, spelling 5 errors, and paragraphing 1 error. Hence, reading a lot before writing becomes one’s solution to eliminate the students’ difficulties in writing text. It is recommended that the students must read more and practice the way to write good text especially in writing recount text. Students must understand well the components in writing a good paragraph, so that the students do not experience problems during the process. In addition, they must also pay more attention to the teacher’s explanation when the teaching and learning process is carried out